Prognostic Value of the Right Ventricular-to-Left Ventricular Volume Ratio in Tricuspid Regurgitation - Robert S. Zhang, MD; Pablo Villar-Calle, MD; Lily Jin, BS; Rachel Axman, MD; Zachary Falk, MD; Mahniz Reza, BA; Annie Tsay, MD, MPH; Giorgia Falco, MD; Andre Cheng, MD; Shmuel Chen, MD, PhD; Jonathan W. Weinsaft, MD; Jiwon Kim, MD (JACC: Advances, 2025)
Background: Tricuspid regurgitation (TR) is associated with right ventricular (RV) remodeling; however, conventional RV metrics may not fully reflect the interplay between the right and left ventricles. Objectives: The aim of the study was to examine the prognostic value of the right ventricular-to-left ventricular volume ratio (RV/LVvol) ratio in TR. Methods: A retrospective analysis was conducted on 949 patients with ≥moderate TR who underwent cardiac magnetic resonance imaging between 2005 and 2024. The RV/LVvol ratio was assessed as a dichotomous variable (normal: <1.27, abnormal: ≥1.27) and by severity strata. Follow-up data, including all-cause mortality, were collected using the Social Security Death Index and electronic medical records. Results: Of the 949 patients, 43.6% had an abnormal RV/LVvol ratio. Among 528 patients with a normal RV end-diastolic volume index, 178 (33.7%) had an abnormal RV/LVvol ratio. Over a mean follow-up of 4.8 ± 4.5 years, 236 patients died. An abnormal RV/LVvol ratio was independently associated with increased mortality after adjusting for covariates (adjusted HR: 1.47, 95% CI: 1.01 to 2.14, P = 0.043). Mortality risk increased with RV/LVvol ratio severity, with severe ratios conferring the highest risk (adjusted HR: 2.20, 95% CI: 1.31-4.76, P = 0.045). The RV/LVvol ratio provided significant incremental prognostic value over conventional RV indices, improving global chi-square from 24.7 (age/sex) to 47.1 with RV ejection fraction, 59.3 with RV end-diastolic volume index, and 68.3 with the addition of RV/LVvol ratio (P = 0.005). Conclusions: The RV/LVvol ratio is a strong predictor of mortality in advanced TR, capturing ventricular remodeling not identified by conventional metrics.